Translation and Cultural Adaptation of the Short-Form Food Frequency Questionnaire for Pregnancy into Brazilian Portuguese - Kasawara, Karina Tamy; Paulino, Daiane S. M.; Bgeginski, Roberta; Cleghorn, Chistine L.; Mottola, Michelle F.; Surita, Fernanda Garanhani (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To translate and culturally adapt the short-form Food Frequency Questionnaire (SFFFQ) for pregnant women, which contains 24 questions, into Brazilian Portuguese.Methods Description of the process of translation and cultural adaptation of the SFFFQ into Brazilian Portuguese. The present study followed the recommendation of the International Society for Pharmacoeconomics and Outcomes Research for translation and cultural adaptation with the following steps: 1) preparation; 2) first translation; 3) reconciliation; 4) back translation; 5) revision of back translation; 6) harmonization; 7) cognitive debriefing; 8) revision of debriefing results; 9) syntax and orthographic revision; and 10) final report. Five obstetricians, five dietitians and five pregnant women were interviewed to contribute with the language content of the SFFFQ.Results Few changes were made to the SFFFQ compared with the original version. These changes were discussed with the research team, and differences in language were adapted to suit all regions of Brazil.Conclusion The SFFFQ translated to Brazilian Portuguese can now be validated for use in the Brazilian population.
Keywords: food consumption; validation studies; pregnancy; translation; adaptation